1992
DOI: 10.1101/gad.6.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids necessary for DNA contact and dimerization imply novel motifs in the papillomavirus E2 trans-activator.

Abstract: The bovine papillomavirus E2 protein regulates viral transcription by binding as a dimer to the DNA sequence ACCGN4CGGT. The dimerization and DNA-binding properties are localized within its carboxy-terminal 85 amino acids (325-410). Utilizing random mutagenesis coupled with phenotypic selection in yeast, functionally important amino acids in the DNA-binding domain were identified. Four trans-activation defective point mutants within a short segment (amino acids 337-344) were DNA binding defective but dimeric. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…A cysteine at position 340 has been shown to be essential for DNA binding. Converting this cysteine into an arginine abolished activation of transcription by BPV1 E2 (43). This cysteine is conserved within all E2 proteins (16).…”
Section: E2 Directly Binds To the Hat Domain Of P300mentioning
confidence: 96%
“…A cysteine at position 340 has been shown to be essential for DNA binding. Converting this cysteine into an arginine abolished activation of transcription by BPV1 E2 (43). This cysteine is conserved within all E2 proteins (16).…”
Section: E2 Directly Binds To the Hat Domain Of P300mentioning
confidence: 96%
“…The full-length BPV-I E2 protein is a 48 kDa phosphoprotein (28) which dimerises spontaneously in the absence of DNA to form stable molecules (29,30). The E2 proteins of all papillomaviruses are organised into three domains, as shown in Figure 1: a well-conserved N-terminal domain involved in transactivation, a central hinge of variable sequence and length, and a C-terminal domain responsible for DNA binding and dimerisation (31).…”
Section: Introductionmentioning
confidence: 99%
“…Recent crystallographic data for the core BPV-l E2 DNA binding domain (C-terminal 85 amino acids) has revealed a novel dimeric DNA binding/dimerisation motif previously undescribed or unpredicted in a eucaryotic transcription factor (32). Two monomers interact to form an eight-stranded antiparallel (3-barrel which is stabilised by an extensive network of hydrogen bonds encompassing a central hydrophobic core where two conserved tryptophans critical for dimerisation (30) are in van der Waals contact. Target DNA is bent over the barrel to align a pair of sy.mmetrically disposed recognition helices with the major groove of the conserved nucleotides in each palindromic half site.…”
Section: Introductionmentioning
confidence: 99%
“…E2 is a site-specific DNA binding protein that dimerizes spontaneously in the absence of DNA (McBride et al, 1989;Prakash et al, 1992) and interacts directly with 12 nucleotide pair palindromic sequences found at conserved locations in all PVs (Fig. 5).…”
Section: E2 Transcriptional Modulatormentioning
confidence: 99%
“…These two functional domains are separated by a somewhat poorly conserved central hinge region of variable length (Giri & Yaniv, 1988;McBride et al, 1991;Prakash et al, 1992). The crystal structure for the C-terminal DNA binding domain of BPV E2 (Hegde et al, 1992) and the NMR structure of HPV-31 E2 (Liang et al, 1996) bound to a double-stranded palindromic recognition sequence have been solved.…”
Section: E2 Transcriptional Modulatormentioning
confidence: 99%